2022
DOI: 10.1111/jdv.18604
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of molecular and serological assays on cerebrospinal fluid for the diagnosis of neurosyphilis

Abstract: Background Many assays are available on cerebrospinal fluid (CSF) for the diagnosis of neurosyphilis (NS) but there is no ‘gold standard’. Objectives The aim of this study was to evaluate different molecular and serological assays used in NS. Methods We evaluated two PCR assays and three serological techniques in parallel on CSF samples collected between 2019 and 2020 from patients suspected of NS. Results The study included 143 patients comprising 30 early NS, 7 late NS and 106 patients without a diagnosis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“… 13 Other relevant reports showed that the sensitivity of nPCR for detecting CSF TP was 42.5% and 27%, and the specificity was 97% and 100%, respectively. 14 , 15 The lower sensitivity of our results may be due to the difference in the study population, whereas Vanhecke’s study included HIV-infected as well as severely immunodeficient syphilis patients, which can exacerbate NS infection. 14 The nPCR test may not be the most sensitive method to diagnose NS.…”
Section: Discussionmentioning
confidence: 86%
“… 13 Other relevant reports showed that the sensitivity of nPCR for detecting CSF TP was 42.5% and 27%, and the specificity was 97% and 100%, respectively. 14 , 15 The lower sensitivity of our results may be due to the difference in the study population, whereas Vanhecke’s study included HIV-infected as well as severely immunodeficient syphilis patients, which can exacerbate NS infection. 14 The nPCR test may not be the most sensitive method to diagnose NS.…”
Section: Discussionmentioning
confidence: 86%
“…A total of 1,140 full-text publications were evaluated for eligibility, 489 were deemed irrelevant to the objective, and 622 lacked sufficient data therefore they were excluded. Ultimately, our meta-analysis was limited to 29 publications ( 2 , 4 , 7 33 ) to perform the quantitative synthesis.…”
Section: Resultsmentioning
confidence: 99%
“…Nine articles reported whether the cases were co-infected with HIV ( 4 , 10 , 11 , 22 , 26 , 27 , 30 32 ). Information on the presence or absence of symptoms in patients with neurosyphilis can be found in 13 studies ( 2 , 4 , 7 , 8 , 11 , 13 , 20 22 , 27 , 28 , 30 , 32 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation